Perceived factors influencing information technology (IT) skills development in undergraduate accounting programme - Senik, Rosmila; Broad, Martin (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This research attempts to understand the process of enhancing IT skills development in undergraduate accounting programme using grounded theory methodology. It aims to gain an insight into the research area from the perspectives of accounting practitioners, accounting educators and accounting students including alumni. The primary data collection methods are focus group, personal interviews, documents reviews and observations. This paper discusses the findings on main factors perceived to influence the development of IT skills in the programme. It suggests that university policy, employers’ expectation, other universities’ IT skills development, quality assurance review and professional examination exemption are the main external factors that influence the IT skills development. More to the point, the internal factors such as educators’ personal motivation and interest, perceived to be more influential in the decision to include and develop IT skills in the teaching process. Thus, it is evident that educators are the major factor influencing the IT skills development initiatives in teaching. These findings make significant contributions towards IT skills development and innovation in accounting education.